The Influence of Music Producing and Creativity on Computational Thinking in Primary School Children - Nardie Fanchamps; Emily Van Gool; Anna Folkertsma; Kim De Meyst (Education Sciences)
Computational thinking (CT) can be developed in a multitude of ways. Well-known examples are plugged-in and unplugged applications that focus primarily on the (combined) usage of visual, textual, or tangible modalities. Less obvious are applications where CT development can be established via an auditory modality, to which the importance of creativity is attributed. When reasoning from such a different contextual perspective, it is interesting to investigate whether the self-creation of electronic music influences CT development and what added value can be attributed to creativity. Therefore, a mixed-methods study was conducted on primary school pupils aged 10 to 13 using FL-Studio Mobile© music-producing software. Quantitative data were obtained using a pre-test–post-test assessment administered via a validated Computational Thinking Test (CTt). Qualitative data were obtained by conducting interviews to ascertain identifiable effects on CT sub-characteristics to determine the influence of creativity and creative thinking and children’s perceptions in this regard. Our results indicate that applying music-making software has measurable effects on CT development, particularly with respect to invoking and using auditory modalities. Notable findings were identified on the CT sub-characteristics “loops”, “conditionals”, “functions”, “nesting”, and “CT tasks required”. Our study shows that producing music using technology stimulates creativity, which seems to be an important parameter for CT development. Differences between girls and boys were observable. Further research on the interaction between CT and creativity, combining different modalities, is recommended.